FOSAMPRENAVIR CALCIUM LOADED DENDRIMERS: FORMULATION DEVELOPMENT, EVALUATION AND HEMOLYTIC TOXICITY STUDIES - SRIVASTAVA, NEHA; MISHRA, YACHANA; MISHRA, VIJAY (International Journal of Applied Pharmaceutics, 2023)
Objective: Dendrimers are the three-dimensional polymeric architectural motif which bestows an advanced platform for drug delivery and drug targeting. Dendrimers are a novel cargo system that can accommodate larger amounts of the drug in its structure by conjugating the drug with terminal amine functional groups. The present work was designed to develop Fosamprenavir calcium-loaded 5th generation poly (propylene imine) (5G PPI) dendrimers for effective treatment of Human immunodeficiency virus. Methods: The drug loading was carried out using a direct method with continuous stirring for 48 h. The sample was characterized using different analytical techniques and also evaluated for drug entrapment, drug release, and release kinetics. The hemolytic toxicity studies were also performed and evaluated based on % hemolysis and surface morphology of RBCs after incubating with the prepared formulation. Results: The Fourier transform infrared (FTIR) and Nuclear Magnetic Resonance (NMR) spectral analysis confirms the conjugation of the Fosamprenavir calcium and dendrimers. Differential scanning calorimetry analysis (DSC) also confirmed the conjugation of the drug with dendrimers. Scanning electron microscopy (SEM) images showcased the spherical floral arrangement of the dendrimer structure. The drug entrapment studies revealed 69.83±0.31% of the drug encapsulated in the dendrimer structure. The drug release studies showed 80.18±0.65% in phosphate buffer pH 7.4 and 68.09±1.78% in acetate buffer pH 5.0. The drug release kinetics showed that the Higuchi release pattern was followed for the release pattern of pH 5 and pH 7.4. The hemolysis study revealed that the conjugation of the drug with 5G PPI dendrimers drastically reduces the hemolysis. Conclusion: Thus, from the studies, it can be concluded that an efficient drug delivery system can be developed for the anti-retroviral drug Fosamprenavir calcium by loading on 5G PPI dendrimers.